Peran Account Officer dan Perkembangan Pembiayaan pada Perbankan Syariah - Syakir, Ahmad (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
The development offinancing of the Islamic banking can not be separated from the role of the accounts officer who became mostimportant marketing personnel on the financial product. By running the functions and role of an account officerat Islamic banking financing the improvement can be realized. It was proven that the increase in 2013 amountedto 80,85% of the total disbursements of Islamic banking or Rp 135, 58 trillion invested in financing activities.Growth is directed to financing the real sector in the form of financing (mudarabah and musharakah), accountsreceivable (murabaha, istisna, and qardh), and in the form of ijarah financing. The development financing in 2013still dominated murabahah receivables amounting to Rp 80,95 trillion or 59.71% followed musharakah financingthat amounted to Rp 25,21 trillion (18.59%) and mudarabah financing amounting to Rp 11,44 trillion (8.44%), andqardh receivables amounting to Rp 11,19 trillion (8.25%). Factor of quality accounts officer was instrumental insupporting the development of Islamic banks, and on the one hand improve the ability of the real sector inemployment.